TROPHY HUNTING: IMPLIKASI PRAKTIK POSTKOLONIALIS TERHADAP TERANCAMNYA EKOLOGI DAN SATWA LIAR DI ZIMBABWE TAHUN 2015 – 2021 - Arum Widyastuti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Trophy Hunting is a hunting activity with the aim of obtaining animal carcasses which are used as symbols of the greatness of the hunters. In its continuation, this practice was carried out by Western hunters from both the United States and Europe who introduced it as the most effective conservation tool for Africa instead of controlling the magnificent megafauna within. This is what makes this practice one of the issues that are currently being discussed because it relates to the environment and the lives of animals in Africa, especially Zimbabwe. Therefore, this study will discuss the implications of trophy hunting activities through a postcolonial approach to the ecological damage of wildlife in Zimbabwe. Furthermore, this research will use anthropocentric environmental ethics to reveal the implications of this practice in more detail. This research uses a descriptive analysis approach with sources obtained from literature studies and analyzed using the discourse analysis method. The findings in this study are trophy hunting is a subtle form of control over megafauna in Africa, especially Zimbabwe, which still legalizes this activity. The persistence of Western power has had a negative impact such as disrupted food chains, declining animal populations, stress levels experienced by animals and other impacts that are also felt by the surrounding community.